PENGARUH BUDAYA ORGANISASI DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN PADA PT. ANUGERAH AGUNG ALAMI WINGS SURYA KLUNGKUNG - Widiarni, Ni Km. Lolita Sri; Martini, Luh Kadek Budi; Verawati, Yenny (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
With the existence of a strong organizational culture in the company and the high self efï€cacy of its employees, it will improve employee performance in the company. This study aims to reexamine the inï€‚uence of organizational culture variables and self efï€cacy on employee performance. The sample in this study were 65 employees at PT. Anugerah Agung Alami Wings Surya Klungkung. Determination of the sample using the method from Slovin. The analytical tool used is multiple linear regression analysis. The results showed that organizational culture variables have a positive effect on employee performance as indicated by a signiï€cance value of 0.000. The self efï€cacy variable also has a positive effect on employee performance as indicated by a signiï€cance value of 0.000.